The Effectiveness of Monetary Policy Transmission Under Capital Inflows. - Jain-Chandra, Sonali (IMF Working Papers., 2012)
The effectiveness of the monetary policy transmission mechanism in open economies could be impaired if interest rates are driven primarily by global factors, especially during periods of large capital inflows. The main objective of this paper is to assess whether this is true for emerging Asia's economies. Using a dynamic factor model and a structural vector auto-regression model, we show that long-term interest rates in Asia are indeed predominantly driven by global factors. However, monetary policy transmission mechanism remains effective in the region, as it operates predominantly through s.